A Feasibility Pump Based Solution Algorithm for Two-Stage Robust Optimization With Integer Recourses of Energy Storage Systems - Zhang, Cuo; Dong, ZhaoYang; Yang, Linfeng (IEEE transactions on sustainable energy, 2021)
To address uncertainties, two-stage robust optimization (TSRO) methods have been widely used for power system operation and planning problems. However, solving TSRO problems with integer recourses of energy storage systems (ESSs) is challenging. This article proposes a feasibility pump based column and constraint generation (FP-CCG) solution algorithm to solve these TSRO problems. In this article, firstly, a TSRO problem of ESS operation with state-of-charge management is formulated. Then, the FP-CCG algorithm is proposed and applied to solve this TSRO problem. Simulation results indicate full solution robustness and high computation efficiency of the proposed FP-CCG solution algorithm.